PRE-PROFESSIONAL TRAINING OF LYCE-LISTERS IN THE SYSTEM CONTINUOUS ECONOMIC EDUCATION ON THE BASIS EDUCATIONAL AND METHODOLOGICAL COMPLEX (NMC) - L.P. Bayrak (Academy of Cognitive and Natural Sciences, 2003)
No abstract.